2018
DOI: 10.1051/shsconf/20184610003
|View full text |Cite
|
Sign up to set email alerts
|

La dyslexie à l’âge adulte : la persistance des difficultés orthographiques

Abstract: Dans cet article, les résultats préliminaires d’une étude plus large sur la production textuelle des étudiants dyslexiques sont présentés. Les productions écrites d’une vingtaine d’étudiants dyslexiques et contrôles sont analysées dans l’objectif de voir ce qu’il en est de la gestion de l’orthographe lexicale et grammaticale. En effet, lors d’analyses antérieures sur les mêmes populations, les étudiants dyslexiques se déclarent en difficultés lorsqu’il s’agit de rédiger un texte, et ce, que ce soit avec l’orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 26 publications
1
24
0
4
Order By: Relevance
“…As mentioned in the literature review, students with dyslexia have difficulties with written text production, whether it be with syntax, text organization, revision, and of course spelling [ 1 , 2 , 4 , 26 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The initial objective of this current study was to complete the existing work on spelling and better identify the spelling difficulties to improve the remediation and to support students with dyslexia more efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As mentioned in the literature review, students with dyslexia have difficulties with written text production, whether it be with syntax, text organization, revision, and of course spelling [ 1 , 2 , 4 , 26 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The initial objective of this current study was to complete the existing work on spelling and better identify the spelling difficulties to improve the remediation and to support students with dyslexia more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that students with dyslexia do not produce polysyllabic words as much as control students do [ 1 , 26 , 50 ] and have a smaller vocabulary [ 1 , 50 , 58 ]. Moreover, their difficulties with writing, and more specifically with spelling [ 26 , 28 , 47 , 48 ], push them to avoid the use of certain words, for which they are not sure about the spelling [ 1 , 26 ]. In contrast to these earlier findings, our analyses ( Section 3.2 ) did not confirm these differences between students with dyslexia and control students.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations